Peran tasawuf akhlaqi dalam mengatasi tantangan moral masyarakat modern - Akmal, Rafi Bastian; Alifiyah, Azzahra Lulu Lulu; Ramadhani, Akhmad Bintang; Faisol, Faisol (Maliki Interdisciplinary Journal, 2024)
This article discusses the importance of inner spirituality in understanding the essence of humanity and life, focusing on Sufism as a form of Islamic mysticism that emphasizes moral development and the purification of the soul. Akhlaqi Sufism, one of the main branches of Sufism, teaches the improvement of good character to achieve a close relationship with God. Historically, early Sufism focused on the psychological and moral aspects of humans, with the ideal of realizing the "insan kamil" or perfect human. This article also highlights modern moral challenges such as materialism and hedonism, and how the values of Akhlaqi Sufism, such as simplicity (zuhud), brotherhood (ukhuwah), love (mahabbah), and self-reflection (muhassabah), can be effective antidotes. To address these challenges, it is recommended that modern society apply these values in daily life to achieve a balance between material and spiritual needs.